If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = 11 + 4x Reorder the terms: 3 + 6x = 11 + 4x Solving 3 + 6x = 11 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3 + 6x + -4x = 11 + 4x + -4x Combine like terms: 6x + -4x = 2x 3 + 2x = 11 + 4x + -4x Combine like terms: 4x + -4x = 0 3 + 2x = 11 + 0 3 + 2x = 11 Add '-3' to each side of the equation. 3 + -3 + 2x = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 11 + -3 2x = 11 + -3 Combine like terms: 11 + -3 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 7u+2u=26 | | 5X-1=-(1-2X) | | x/103 | | (3/2)x-1/2=5/6 | | (2x+1)(5-6x)=3x(4x-1) | | -12+7x=18+4x | | (25x^2)+30x+9=0 | | 15-14g=-3-17g | | 6(3-x)-2(4-x)=0 | | 14x-4=9x+1 | | (4x^2)-4x+1=0 | | 9p+7=10p+10 | | 4x+12=5x+28 | | 4+12=5x+28 | | 3(x-8)+2= | | 3a-7=7a+25 | | (-4x^2)+x+3=0 | | (2x-3)(5-6x)=3x(4x-1) | | 5y=290 | | 3x-10=6x-2 | | 7(x-4)-7=15 | | 9h=55 | | x/(x-16) | | -16=2y-2 | | ln(5.8)=x | | 18/[4x(15-13)-5] | | 5(x+y)=5v+5y | | X+(x*.05)=36.75 | | 3+4x=2x+16 | | -6p-7p=6-8p-8p | | -7a-6a=-7a | | x^2-x-25=5 |